MENINGKATKAN HEADING DENGAN BOLA KARET DALAM PERMAINAN SEPAK BOLA DI SDN 14 SUNGAI PUTAT - Muluri, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This study aims to determine the level of learning outcomes in a football heading using a rubber ball on a fifth grade students of SDN 14 Sungai Putat. Forms of research is classroom action research. Subjects in this study were students of class V SDN 14 Sungai Putat. The total number of class students are as many as 26 students consisting of 14 boys and 12 female student . Based on the results of the study in the first cycle are the result of the thoroughness with the number of 18 students, or about 69%, and students who have not completed amounted to 8 students or by 31%. While the second cycle there is a category of student outcomes to complete all of the graduating students, totaling 26 students or equal to 100% and unresolved amounted to 0 or does not exist Keywords: Heading, Ball Rubber